Response of Sansevieria trifasciata cuttings On the Soaking Time of Vigna radiata Sprouts Extract - Irawati Utami, Inayah; Siti Wahyuni (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2025)
This study aimed to determine the effect of soaking time of mung bean (Vigna radiata) sprout extract on the growth of snake plant (Sansevieria trifasciata) leaf cuttings. The study was conducted at the Faculty of Agriculture's screen house, UGJ Cirebon used a Completely Randomized Design (CRD) with five treatments of immersion duration (10, 20, 30, 40, and 50 minutes) each repeated five times. The parameters observed included root length, time to shoot emergence, number of shoots, leaf thickness, chlorophyll content, and plant growth rate. The analysis results showed that the immersion duration significantly affected root length, initial shoot emergence, and number of shoots, especially at 40 and 60 days after planting. The best treatment was obtained at 30 minutes of immersion which consistently produced the most optimal root and shoot growth. Meanwhile, there was no significant effect on leaf thickness, chlorophyll content, and plant growth rate in all treatments. The phytohormone content in mung bean sprout extract such as auxin, cytokinin, and gibberellin is thought to play a role in stimulating root and shoot growth in the early phase of snake plant cutting propagation. This study proves that natural PGR from mung bean sprouts has the potential as an environmentally friendly alternative in supporting the vegetative propagation of ornamental plants.